Analysis of radioisotope concentrations in sediments using γ-ray spectrometry. (21st March 2006) - Kullab, M.; Ismail, A.; Abu-Rukah, Y.
The concentrations of some naturally occurring radioisotopes in sediments of the Kufranja river basin in Jordan were determined by means of γ-ray spectrometry with precise calibration of energy and efficiency. The nuclides' concentrations were found by either direct measurement of their activities, as in the case of 226 Ra and 40 K, or through the measurements of the activities of their daughters with short half-lives, as in the case of 238 U and 232 Th. Furthermore, the hazard index, the radium equivalent activity and the absorbed dose rate for each of these nuclides had been calculated. It turned out that the concentrations of radioisotopes in sediments of the studied area were below the standard limits and the human effective dose equivalent ranged from 23.8 to 35.7 µSv/yr.